2021
DOI: 10.3390/pr9020359
|View full text |Cite
|
Sign up to set email alerts
|

Wood Fuel Procurement to Bioenergy Facilities: Analysis of Moisture Content Variability and Optimal Sampling Strategy

Abstract: Moisture content is the most relevant quality parameter for wood fuels. Effective and fast determination of moisture of incoming feedstock is essential in the management of bioenergy facilities. The availability of fast and reliable moisture meters based on innovative technologies simplifies this task. However, in Mediterranean conditions the inherent variability of wood fuels calls for a careful sampling strategy if representative results are required while facing acceptable analytic costs. The present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The physico-chemical properties of biochar, used as a renewable energy source, are essential for the optimalization of its production use [ 47 , 48 , 49 ]. Moisture and ash content are important parameters of the biochar quality, which precise determination is essential [ 50 ] as well as accurate determination of calorific value [ 51 ]. The fraction of individual elements (CHNS) has a major influence on the thermal output of the combustion plant [ 52 ], but also on the resulting emission concentrations during combustion of biochar fuels [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The physico-chemical properties of biochar, used as a renewable energy source, are essential for the optimalization of its production use [ 47 , 48 , 49 ]. Moisture and ash content are important parameters of the biochar quality, which precise determination is essential [ 50 ] as well as accurate determination of calorific value [ 51 ]. The fraction of individual elements (CHNS) has a major influence on the thermal output of the combustion plant [ 52 ], but also on the resulting emission concentrations during combustion of biochar fuels [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ligneous biofuels may possess a high initial water content of 50 wt% to 65 wt% [20]. Factors such as storage duration, season, assortment and rain protection have a statistically significant influence on water content of woody biomass [21,22]. The water content of fresh wood chips is approximately 50 wt%, but this could vary between 66 wt% and 36 wt% according to storage conditions [21].…”
Section: Introductionmentioning
confidence: 99%
“…This information can be used to check the accuracy of the modelled MC values and to make adjustments to the drying model(s) if required. Leoni et al [50] found that the relatively new MC measurement technique of magnetic resonance was able to provide rapid MC measurements comparable in accuracy with those of the standard oven-drying technique and without the need for fuel-specific calibration required by tools based on near-infrared.…”
Section: Discussionmentioning
confidence: 99%